2017
DOI: 10.18203/2349-2902.isj20174523
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathology study of necrotizing fasciitis with special reference to Fournier’s gangrene

Abstract: Background: Necrotizing fasciitis including Fournier’s gangrene is an uncommon, critically serious infection of the subcutaneous tissue and fascia with relative sparing of the skin and muscle. Despite modern supportive measures, the reported mortality rate still is high and this is due to part to the aggressive nature of the infection. The present study was performed upon 50 patients to study clinicopathology of necrotizing fasciitis with special reference to Fournier’s gangrene. Methods: This cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…13 The LRINEC scoring can help in predicting septic shock (cut-off point of 5 points with sensitivity 82% and specificity 38%) and mortality (cut-off point of 8 points with sensitivity 81% and specificity 36%) A previous study by Fernando et al reported the accuracy of NF diagnosis with LRINEC scoring of 6 as a cut-off point has a sensitivity of 68.2% and specificity of 84. 8,13 while a cut-off point score of 8 has a sensitivity of 40.8% and specificity of 94.9%. 5 Although a previous study by Goh et al stated that clinical suspicion is superior to laboratory testing or LRINEC score, this cannot be applied in our case due to the masking effect of prior leprosy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The LRINEC scoring can help in predicting septic shock (cut-off point of 5 points with sensitivity 82% and specificity 38%) and mortality (cut-off point of 8 points with sensitivity 81% and specificity 36%) A previous study by Fernando et al reported the accuracy of NF diagnosis with LRINEC scoring of 6 as a cut-off point has a sensitivity of 68.2% and specificity of 84. 8,13 while a cut-off point score of 8 has a sensitivity of 40.8% and specificity of 94.9%. 5 Although a previous study by Goh et al stated that clinical suspicion is superior to laboratory testing or LRINEC score, this cannot be applied in our case due to the masking effect of prior leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 One of the rare comorbidities ever reported in NF is leprosy. 8 Leprosy enhances diagnostic challenges in NF due to its hypoesthesia clinical features that mask severe localized pain, a characteristic feature of NF. 7 We report a case of NF with the history of prior leprosy with marked hypoesthesia in the limited resources.…”
Section: Introductionmentioning
confidence: 99%